KAJIAN UNSUR INTRINSIK CERITA RAKYAT DI DESA PADANG TIKAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Effiyadi, Effiyadi; Effendy, Chairil; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated that the folklore that existed in Padang Tikar community of BatuAmparsubdistrict is considered as something that must be known by the next generation, because they consider it a culture that needs to be preserved. Therefore, this folktale is preserved, for future generations to know the story.The problem in this research is to study, describe the structure of the text and analyze the intrinsic elements of folklore in the village of Padang TikarBatuAmpar Sub-district Kubu Raya RegencyThis research uses descriptive method and qualitative research forms on the text of oral literary stories of the community in the village of Padang TikarKecamatanBatuAmparKabupatenKubu Raya.The results of the analysis show that the 7 Folk Story owned by the community in the village of Padang TikarBatuAmpar Sub-district of Kubu Raya Regency contains intrinsic elements that can be revealed by using qualitative descriptive approach. The aspects studied are the theme, plot, character, background and mandate. The results of this study can be implemented in the Indonesian language learning Curriculum 2013 unit level SMA / MA which refers to the Core Competence and Basic Competence (KI / KD) contained in the syllabus teaching Indonesian Class X Odd Semester. Researchers hope other researchers who take about folklore as the object of research can examine more deeply because there are still many things that have not been studied. Keywords: intrinsic elements, values, functions, abstinence forbidden